APLIKASI SISTEM PAKAR DIAGNOSIS PENYAKIT PADA GIGI - Seruni, Dewi; Rahmawati, Linda Suvi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Expert system is one branch of artificial intelligence that mimics the way to learn how to think an expert in solving a problem. Artificial intelligence is one of the fields of computer science which utilizes intelligent computer so that it can behave like a human. Computer science to develop software and hardware to mimic human actions. Simulated human activities such as reasoning, vision, learning, problem solving, natural language understanding, and so on. By definition, artificial intelligence technology studied in fields such as Robotics (Robotics), Computer Vision (Computer Vision), Natural Language Processing (Natural Language Processing), Pattern Recognition (Pattern Recognition), Artificial Neural Systems (Artificial Neural Systems), Introduction voice (speech recognition), and expert systems (Expert System). Application of Expert System is a software package that discusses how to diagnose diseases of the teeth. The programming language used to make the expert system application is using PHP with MySQL database. Accordance with the programming language that is used it will be displayed in the interface which provides information for the user to visually shape.Keywords : Expert systems , dental disease , Forward chaining